Analysis of the development scenarios and greenhouse gas (GHG) emissions in China's aluminum industry till 2030. (25th March 2021) - Li, Shupeng; Zhang, Tingan; Niu, Liping; Yue, Qiang
Abstract: The rapid economic growth and industrialization in China have induced a large aluminum demand since 1990. Faced with the complex international economic situation recently, China proposed a new national development pattern of "with the big domestic cycle as the main body, the domestic and international double cycles promote each other". Under the guidance of this kind of macro-control thinking, China's aluminum industry (CAI) may also need to make corresponding adjustments to future development policies. This paper used dynamic material flow analysis (MFA), regression analysis, and normal life distribution to estimate the domestic consumption, scrap generation, and in-use stock of aluminum from 1990 to 2030 in China. The results show that the amount of domestic consumption, scrap generation, in-use stock has been increasing from 1990 and are expected to reach 54, 19, and 640 Tg in 2030, respectively. Then, the scenario analysis method was adopted to discuss the impact of reducing external circulation (export volume) of aluminum on China's aluminum production and related GHG emissions. The results of the scenario analysis indicate that effective measures to reduce the export of aluminum products could lead to significant mitigation in China's primary aluminum production and GHG emissions. Besides, the amount of recycled aluminum will gradually increase in the future, and the proportion of it will reach about 30% by 2030 (22% in 2017) even under the most unfavorable scenario. Relying on the growth of recycled aluminum and the decline in exports of aluminum products, CAI is expected to reach the peak of GHG emissions around 2030, on the premise of meeting the domestic strong aluminum consumption.